Anthropomorphic Brain Models Based on Magnetic Resonance Imaging - V. V. Kabachek; N. S. Davydova; M. M. Mezhennaya; M. V. Davydov (Цифровая трансформация, 2022)
The article is devoted to the creation of a method for generating anthropomorphic brain models based on magnetic resonance imaging. The selection of the magnetic field amplitude for transcranial magnetic stimulation (TMS) is carried out through modeling using the finite element method (FEM). These FEM models graphically demonstrate information on the distribution of the magnetic field and, therefore, on the occurring neurophysiological and behavioral changes based on the dose of the TMS, the specific resistance of the head tissue and its anatomy. Thus, these models are an integral tool used to design, configure, and program TMS devices, as well as to study parameters such as magnetic field strength and tension. A distinctive aspect of this work is the quality of the resulting head models. When creating the calculated FEM models, an MRI image of the head was used to perform segmentation in the FreeSurfer environment. Next, the image was converted in the Matlab environment. After the assembly of the head model in COMSOL Multiphysics, the TMS was simulated. The results of the transformations is a head model made in the form of a three-dimensional grid, which is suitable for modeling. The obtained data can be used to personalize the TMS method in medicine.